Eksplorasi Tumbuhan dalam Ritual Mappacci Suku Bugis di Wajo: Memahami Kekayaan Etnobotani Budaya Lokal Masyarakat - Ahmad Yani; Rizal Irfandi; Syamsu Rijal; Nurcaya Nurcaya (Jurnal Penelitian Pendidikan IPA, 2024)
Mappacci is one of a series of traditional wedding rituals of the Bugis tribe. This research aims to classify and identify various types of plants and the meaning of their use in the traditional rituals of the Bugis mappaci tribe. This research method is descriptive qualitative. Data collection through observation, interviews and documentation. The results of the research found 7 types of plants in the Mappacci traditional ritual. The plant species used are Pacar (Lawsonia inermis L), Jackfruit (Artocarpus heterophyllus Lam), Banana (Musa paradisiaca L), Rice (Oryza sativa L), Coconut (Cocos nucifera L), Palm (Arenga pinnata Merr) and Cotton (Ceiba pentandra) which includes 6 families, namely Lythraceae, Moraceae, Musaceae, Poaceae, Arecaceae, Bombacaceae. The plant parts used are leaves (75%), fruit (50%), seeds (25%), sap (25%). The plants used in the Mappacci traditional rituals of the Bugis tribe have a philosophical meaning of goodness. Community knowledge in the use of these plants is a tradition passed down from generation to generation from their ancestors